Management of irrigation levels and injected fertilization and its effect on the growth and productivity of tomato crops inside greenhouses - Rehab Mohammed Arbi Altawati,; Aedh Abduliah Abdulwahhab Dhu,; Abdulkarim Imhemed Abushaala, (African Journal of Advanced Pure and Applied Sciences, 2025)
A field experiment was conducted during the winter growing season on October 21, 2024, inside a protected greenhouse (plastic tunnel) to investigate the effects of irrigation levels (100%, 75%, and 50% of the calculated crop evapotranspiration, ETc) and fertigation treatments (three NPK combinations) on the vegetative growth and yield of tomato plants (Solanum lycopersicum L.). The experiment was laid out in a factorial arrangement using a Randomized Complete Block Design (RCBD) with three replications. Measurements included stem diameter, leaf count, number of floral clusters, fruit count per plant, and yield per hectare. The results revealed that full irrigation (100% ETc) combined with balanced fertigation (F1) resulted in the highest values for stem diameter, leaf number, floral cluster count, fruit number per plant, and maximum yield (85.76 tons/ha). In contrast, reducing irrigation to 50% ETc along with low-level fertigation led to a statistically These findings underscore that applying balanced NPK fertigation in conjunction with optimal irrigation (100% ETc) represents the most effective strategy for achieving vigorous growth and high productivity of tomatoes under greenhouse conditions